Pengaruh ROA, NPM, GPM dan Inflasi terhadap ROE pada Bank Syariah di Indonesia - Oktaviani; Mu'arrif, Zul Ihsan; Syukrawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research was conducted in order to determine the effect of ROA(X1), NPM(X2), GPM(X3) and Inflation(X4) on ROE(Y) in Islamic banks in Indonesia. The research uses a quantitative approach with descriptive and associative strategies. Supporting information and measurements based on secondary data and statistical software. The population in this research is Islamic financial institutions in Indonesia and the sample is 4 Islamic financial institutions in Indonesia. Then the data obtained comes from the financial reports of 4 banks for the last five years and is calculated using profitability ratio calculations, namely calculating ROA, ROE, NPM, GPM. The external variable used is inflation. Inflation information is obtained from the Bi.go.id website. From the results of calculating profitability ratios, this information is then handled using SPSS by carrying out classical assumptions, regression tests and hypothesis tests. The test results show that the variable ROA(X1) has t = 2.249 > r table = 0.4438 with a significance value of 0.0400 <0.05, the variable NPM (X2) has a t value of 0.901> R table = 0.4438 with significance value 0.382> 0.05. The GPM variable (X3) includes t = 0.883 > R table = 0.4438 with a significance value of 0.391 > 0.05, the inflation variable (X4) has a value of t = -1.100 > R table = 0.4438 with a significance value of 0.289 > 0 .05. Based on the tests carried out in this research, it appears that the ROA (X1), NPM (X2), inflation (X4) factors have an effect on ROE and the GPM variable (X3) has no effect on ROE in Islamic banks in Indonesia.